Qualidade de sêmen criopreservado de carneiros alimentados com ácidos graxos poli-instaurados complexados com sais de cálcio - Santos, Tarsizio da Silva (2013)
Sources of lipids based on polyunsaturated fatty acids have been used for qualitative improvement of cryopreserved semen. Supplementation of diets with unsaturated oils for ruminants is recommended with the addition of a protector to facilitate their absorption. The objective of this study was to evaluate the influence of different levels of polyunsaturated fatty acids in the diet on the fatty acid view and quality of the semen cryopreservation of rams. Twenty-four Santa Inês raced rams were randomly distributed into four groups fed with isoproteic diets: G0 - without polyunsaturated fatty acids complexed with calcium salts (Ca-PUFA) and G3, G6 and G9 with Ca-PUFA levels in 3, 6, 9%, respectively. The semen was collected and frozen in French straws in the following periods: 0 (P0), 30 (P30), 60 (P60) and 90 (P90) days beginning the administration of diets. The fresh semen samples were analyzed for motility subjective, and the fatty acid profile, while samples of frozen-thawed semen were analyzed for sperm kinetics in a computerized system, evaluation of sperm membranes integrity, sperm capacitation and acrossome reaction. The results were subjected to a multivariate analysis including comparison tests of average between treatments on fatty acid profile in the P90, with the correlation of coefficient for axis 1 and 2 NMS and correlation of coefficient of the parameters of sperm for axis 1 and 2 NMS with a Monte Carlo test, at the significance level of 5%. It was identified in experiment 1 were identified lower proportions of stearic acid, oleic, -linolenic, arachidonic sperms in groups of rams treated with 9% Ca-PUFAs (G9) when compared to the control group (G0) after 90 days of administration diet. It was observed in experiment 2 a lower average kinetic parameters ALH and VCL of semen from rams fed with 9% diet. It was concluded that supplementing the diet with 9% Ca-PUFA after 90 days, produces no changes in the kinetic parameters such as curvilinear velocity and amplitude of lateral head of semen cryopreservation produced by rams, even containing lower proportions of oleic, - linolenic and arachidonic.